Practical Enzymology - Bisswanger, Hans (Wiley-VCH, 2019)
assay; enzyme assays; enzymology; enzymes; catalysis; biochemistry; chemical biology; biochemical assay; protein determination; biotechnology; organic chemistry; immobilized enzymes; multi-enzyme complexes; binding measurements; immunoassays